Answer:
x = 4, y = 3
Step-by-step explanation:
Equating corresponding coordinates , gives
2x = 8 ( divide both sides by 2 )
x = 4
and
3y = 9 ( divide both sides by 3 )
y = 3
Answer:
3![\sqrt{6}](https://tex.z-dn.net/?f=%5Csqrt%7B6%7D)
Step-by-step explanation:
using the rule of radicals
×
⇔ ![\sqrt{ab}](https://tex.z-dn.net/?f=%5Csqrt%7Bab%7D)
![\sqrt{54}](https://tex.z-dn.net/?f=%5Csqrt%7B54%7D)
=
=
×
= 3![\sqrt{6}](https://tex.z-dn.net/?f=%5Csqrt%7B6%7D)
When you factor this problem you get:
(3x+5)(x+10)
Answer and explanation:
Statement - If the difference of two numbers is even then so is their sum.
Let the two even numbers be '2m' and '2n' with m and n are integers.
The difference of two number is
![2m-2n=2(m-n)](https://tex.z-dn.net/?f=2m-2n%3D2%28m-n%29)
Now, The sum of the numbers is
![2m+2n=2(m+n)](https://tex.z-dn.net/?f=2m%2B2n%3D2%28m%2Bn%29)
Let
where k is an integer
Then,
which is also an even number as 2 is multiplied with it.
So, If the difference of two numbers is even then so is their sum.
For example -
Let two even number 2 and 4.
The difference is
, 2 is even.
The sum is
, 6 is even.
Answer:
12.9
Step-by-step explanation:
Given data
Give the expression
F(t)=8.50(1.15)^3
Let us solve the term in the bracket
F(t)=8.50*1.520875
F(t)=12.9
Hence the final answer is 12.9